Cross-domain negative effect of work-family conflict on project citizenship behavior: Study on Chinese project managers. Issue 3 (April 2018) - Xia, Nini; Zhong, Rui; Wang, Xueqing; Tiong, Robert
Abstract: This research aims to examine whether and how the bidirectional work-family conflict—work-to-family conflict (WFC) and family-to-work conflict (FWC)—would influence project citizenship behavior (PCB) among Chinese project managers. We proposed hypotheses regarding the relationships between work-family conflict and PCB and the mediating effects of project commitment, which considered the role of national context. Data collected from 154 Chinese project managers were analyzed using structural equation modeling. It was found that FWC had negative relationships with all the three chosen PCBs, i.e., helping behavior, individual initiative, and relationship maintenance, and project commitment mediated these relationships. However, no negative influences of WFC on the three PCBs and project commitment were found. Further comparisons of effects of WFC and FWC on PCBs and project commitment indicated that Chinese project managers were less subject to the negative impacts of WFC. Overall, our results supported the cross-domain negative effect but rejected matching-domain negative effect of work-family conflict among Chinese project managers. We extend understandings of work-family conflict and PCB in the project context, and verify the importance of national context in interpreting work-family issues. Practical suggestions are also discussed regarding increasing project managers' PCB. Highlights: The influences of WFC and FWC on PCB are examined. The role of national context in the effects of work-family conflict is verified. FWC is negatively associated with PCB, with project commitment as a mediator. No negative influences of WFC on PCB and project commitment were found.